KOMUNIKASI KEBIJAKAN PEMBANGUNAN PERTANIAN BERAS HITAM DALAM PEMBERITAAN MEDIA ONLINE: ANALISIS NVIVO 11 - Rahmawati Zulfiningrum; nfn Sumardjo; Amiruddin Saleh; Ivanovich Agusta (Jurnal Penelitian Komunikasi dan Pembangunan, 2019)
The problems of the degenerative diseases such as heart attacks and diabetes in Indonesia become a threat to public health and require alternative food like black rice. Black rice is an excellent commodity that potential to resolve these health problems, therefore these matter become a challenge for the local government for its development. This study examines the policy communication process in the development of black rice farming in Sirampog Sub-district, Brebes District. The used data came from reporting news on online media and field data from interviews that were analyzed using NVivo 11. The study results showed that the importance of local government commitment of Brebes, facility support, effectively communication process, and sustainable development. Effective communication in the form of participatory communication is to increase community involvement in developing black rice programs. The communication patterns design need to pay attention the main factors such as improving the quality of black rice, cultivation to maintain the purity of local varieties, changes in cropping patterns and application of agricultural technology. By the communication process of participatory program, government policies, and publications from online media has the opportunity to increase the development of black rice farming in Brebes Distric.